Innovations in Nutrition Education Programs to Increase Public Awareness of Nutritional Health - Inayatul Fitri (Professorline, 2024)
Optimal nutritional health is key to preventing various health problems. This article discusses innovations in nutrition education programmes that aim to increase public awareness of the importance of nutritional health. It presents new strategies in the design and implementation of education programmes that can effectively increase knowledge and positive behaviours related to nutrition. By utilising technological, interactive and community-based approaches, the article explores how such innovations can more effectively achieve the goal of empowering people to make better nutrition decisions. The findings from this article are expected to provide valuable guidance for the development and improvement of nutrition education programmes at various levels of society, contributing to the overall improvement of nutritional health.